Lymphangiography and Lymphatic Interventions - Yadav, Ajit; Jain, Yajush; Narkhede, Amey; KM, Mahendra; Gupta, Arun (Journal of Clinical Interventional Radiology ISVIR, 2021)
Compared with the traditional pedal lymphangiography, intranodal lymphangiography and MR lymphangiography have made imaging of the lymphatic system less challenging. Improvements in imaging and availability of newer catheters have allowed embolization of lymphatic system much more feasible that previously envisioned. In this article, we briefly review the anatomy, imaging, and current and future of lymphatic interventions.
Keywords: lymphangiography; embolization; chylous leak; lymphatic embolization; lymphatic system